Hubungan Antara Minat Belajar Dan Kemandirian Belajar Dengan Prestasi Belajar Bahasa Inggris Siswa SMA Muhammadiyah 1 Surakarta - Hartono, Reiza Nuary Asih; , Susatyo Yuwono ,S. Psi, M. Si., Psi (2017)
The main purpose of learning English is intended to improve students ability in communication with English, either verbally and written. English is essential competencies required to face the challenges of the global world education. In the process of learning, the majority of students have not been able to listen, speak, read and write well even with simple sentences, many students do not like the English lessons. Learning achievements used in many manifold, such as feedback for teaching , for diagnostic purpose, guidance counseling, for the purpose of selection, for purpose of placement or majors, to determine the contents of curriculum, and to define the school policy. The purpose of this research was to determine the relationship between learning by interest and independent learning with learning English achievements. This study used quantitative research with correlational method. Population research were 328 students on grade 2 in senior high school of Muhammadiyah 1 Surakarta. Class XI consists of class XI IPA 1 - XI IPA 3 which have 120 students, XI IPS 1 - XI IPS 5 which have 208 students. Samples or subjects taken in this research were 165 students (132 students were present, 33 students were absent) with cluster random sampling consisted of XI IPA 1 (37 students), XI IPA 2 (31 students), XI IPS 2 (28 students ) and XI IPS 3 (36 students). Data collection used a scale of interest in learning, independent learning and document the value of learning English achievement, while analysis of data using Non-Parametric Correlation Kendall's. Conclusion of research is there was not relationship between interest in learning and learning English achievement, there is no relationship between independent learning and learning English achievement. Category learning English achievement 37.90% (50 students) is quite good. 62.10% (82 students) is quite the learning achievement.